Feasibility of board tilt angle on critical organs during hippocampus-sparing whole-brain radiotherapy - sengul, aycan; Toksoy, Turgay; Kandemir, Recep; Karaali, Kamil (International Journal of Computational and Experimental Science and Engineering, 2024)
The objective of this study was to investigate the impact of altering the board angle on critical organ doses during whole-brain irradiation. Tomography images of the head region of the rando phantom were taken at angles of 0°, 10°, 20°, 30°, and 40°. Target volume (PTV) and organ at risk (OAR) contours were created on CT images using RTOG 0933 criteria. Tomography images of the head region of the rando phantom were taken at angles of 0°, 10°, 20°, 30°, and 40°. Target volume (PTV) and critical organ contours were created on CT images using RTOG 0933 criteria. During this comparative study, we aimed to achieve a standardized dose distribution in the PTV. We evaluated the doses received by D2 (minimum dose received by 2% of the target volume), D98 (minimum dose received by 98% of the target volume), D50 (dose received by 50% of the target volume), and organs at risk (OAR) in the PTV using CT scans taken at different angles. Additionally, we compared the homogeneity index (HI), conformity index (CI), and treatment time (MU) values. This method aimed to decrease the dose of the OAR region near the target volume, specifically the hippocampus. Our findings indicate that a board angle of 300 offers the greatest protection in terms of critical organ doses.